Bronchiectasis in patients with chronic obstructive pulmonary disease in a tertiary care center in North-East India - Sangtam, Noklangkumla; Haorongbam, Sunanda; Silpa, Kshetrimayum; Singh, Yumnam Priyabarta (International Journal of Advances in Medicine, 2020)
Background: Bronchiectasis is common in patients with Chronic Obstructive Pulmonary Disease (COPD). COPD with bronchiectasis has been considered a phenotype with worse lung function and more severe exacerbations. There is scarce literature on the characteristics and optimal management of such patients. Methods:Patients with COPD reporting within the one-year study period were subjected to High Resolution Computed Tomography (HRCT) scan of the thorax. Sputum was sent for Gram-stain and culture/sensitivity for patients found to have bronchiectasis. Bronchiectasis Severity Index (BSI) was calculated using the online BSI calculator. Association between presence of bronchiectasis and gender, lung function and frequency of exacerbations was statistically analysed. Results: Total 62 patients with COPD were enrolled. Bronchiectasis was present in 11 (17.7%) patients. The most common bacterial isolate from sputum of patients with bronchiectasis was Haemophilus influenza (54.54%). The prevalence of bronchiectasis was more in females (19.45% compared to 15.4% in males), but this association was not found to be statistically significant(p=0.748). Forced Expiratory volume in 1st second (FEV1) was found to be significantly lower in patients with bronchiectasis (p<0.05). There was increased frequency of exacerbations among patients with bronchiectasis. This association was however not found to be statistically significant (p=0.765), 1 (9.1%) patient had low BSI score (0-4), 3 (27.3%) patients had intermediate BSI score (5-8) and 7 (63.3%) patients had high BSI score (≥9). Conclusions:The presence of bronchiectasis in COPD is a phenotype associated with a poor clinical course. The characteristics of this co-existence are largely unknown. More studies are required to properly characterize and manage patients with this coexistence. <!–[if !supportLists]–>1. <!–[endif]–>Global Initiative for Chronic Obstructive Lung Disease Global Strategy for the Diagnosis, Management, and Prevention of Chronic Obstructive Pulmonary Disease. 2014. Available at: http://wwwgoldcopdorg/. Accessed 1 February, 2018 <!–[if !supportLists]–>2. <!–[endif]–>Global Initiative for Chronic Obstructive Lung Disease. Global strategy for the diagnosis, management, and prevention of chronic obstructive pulmonary disease 2019 report. Available at: https://goldcopd.org/wp-content/uploads/2018/11/GOLD-2019-v1.7-FINAL-14Nov2018-WMS.pdf. Accessed 24 January 2019. <!–[if !supportLists]–>3. <!–[endif]–>Martínez-García MA, de la Rosa Carrillo D, Soler-Cataluña JJ, Donat-Sanz Y, Serra PC, Lerma MA, et al. Prognostic value of bronchiectasis in patients with moderate-to-severe chronic obstructive pulmonary disease. Am J Respirat Crit Care Med. 2013 Apr 15;187(8):823-31. <!–[if !supportLists]–>4. <!–[endif]–>Pasteur MC, Bilton D, Hill AT. British Thoracic Society guideline for non-CFbronchiectasis. Thorax. 2010 Jul 1;65(Suppl 1):i1-58. <!–[if !supportLists]–>5. <!–[endif]–>Mao B, Lu HW, Li MH, Fan LC, Yang JW, Miao XY, et al. The existence of bronchiectasis predicts worse prognosis in patients with COPD. Scientific reports. 2015 Jun 16;5:10961. <!–[if !supportLists]–>6. <!–[endif]–>Jin J, Yu W, Li S, Lu L, Liu X, Sun Y. Factors associated with bronchiectasis in patients with moderate-severe chronic obstructive pulmonary disease. Med (Baltimore) 2016;95(29):e4219. <!–[if !supportLists]–>7. <!–[endif]–>Du Q, Jin J, Liu X, Sun Y. Bronchiectasis as a co morbidity of chronic obstructive pulmonary disease: a systematic review and meta-analysis. PLoS One. 2016;11(3):e0150532. <!–[if !supportLists]–>8. <!–[endif]–>Ni Y, Shi G, Yu Y, Hao J, Chen T, Song H. Clinical characteristics of patients with chronic obstructive pulmonary disease with co morbid bronchiectasis: a systemic review and meta-analysis. Int J Chron Obstruct Pulmon Dis. 2015;10:1465-75. <!–[if !supportLists]–>9. <!–[endif]–>Loebinger MR, Wells AU, Hansell DM, Chinyanganya N, Devaraj A, Meister M, et al. Mortality in bronchiectasis: a long-term study assessing the factors inﬂuencing survival. Eur Respir J. 2009;34(4):843-9. <!–[if !supportLists]–>10. <!–[endif]–>Rakhimova E, Wiehlmann L, Brauer AL, Sethi S, Murphy TF, Tummler B. Pseudomonas aeruginosa population biology in chronic obstructive pulmonary disease. J Infect Dis. 2009;200(12):1928-35. <!–[if !supportLists]–>11. <!–[endif]–>Chalmers JD, Goeminne P, Aliberti S, McDonnell MJ, Lonni S, Davidson J, et al. The bronchiectasis severity index. An international derivation and validation study. Am J Respir Crit Care Med. 2014;189(5):576-85. <!–[if !supportLists]–>12. <!–[endif]–>Dou S, Zheng C, Cui L, Xie M, Wang W, Tian H, et al. High prevalence of bronchiectasis in emphysema-predominant COPD patients. Int J Chron Obstruct Pulmon Dis. 2018;13:2041-7. <!–[if !supportLists]–>13. <!–[endif]–>Ramakrishna R, Ambica A. Association of Bronchiectasis in Moderate to Severe COPD patients attending Katuri Medical College Hospital, Guntur from 2011-2013. J Evidence Based Med Healthcare 2015;2(13):2062-76. <!–[if !supportLists]–>14. <!–[endif]–>Martinez-Garcia MA, Soler-Cataluna JJ, Donat Sanz Y, Catalan Sera P, Agramunt Lerma M, Ballestin Vicente J, et al. Factors associated with bronchiectasis in patients with COPD. Chest 2011;140(5):1130-7. <!–[if !supportLists]–>15. <!–[endif]–>Kumar S, Singh GV, Gupta RK, Singh H, Prakash G. To estimate the prevalence of bronchiectasis in COPD patients. IOSR JDMS. 2018;17(3):82-90. <!–[if !supportLists]–>16. <!–[endif]–>Woodhead M, Blasi F, Ewig S. Guidelines for the management of adult lower respiratory tract infections. Eur Respir J. 2005;26:1138-80. <!–[if !supportLists]–>17. <!–[endif]–>Patel IS, Vlahos I, Wilkinson TM, Lloyd-Owen SJ, Donaldson GC, Walks M, et al. Bronchiectasis, Exacerbation indices and Inflammation in Chronic Obstructive Pulmonary Disease. Am J Respir Crit Care Med. 2004;170(4):400-7. <!–[if !supportLists]–>18. <!–[endif]–>Chen YH, Sun YC. Bronchiectasis as a co morbidity of chronic obstructive pulmonary disease: implications and future research. Chin Med J (Engl). 2016;129(17):2017-9. <!–[if !supportLists]–>19. <!–[endif]–>Gatheral T, Kumar N, Sansom B. COPD-related bronchiectasis; independent impact on disease course and outcomes. COPD. 2014;11(6):605-14. <!–[if !supportLists]–>20. <!–[endif]–>Goeminne PC, Nawrot TS, Ruttens D, Seys S, Dupont LJ. Mortality in non-cystic fibrosis bronchiectasis: a prospective cohort analysis. Respir Med. 2014 Feb 1;108(2):287-96. <!–[if !supportLists]–>21. <!–[endif]–>Hurst JR, Elborn JS, De Soyza A. COPD–bronchiectasis overlap syndrome. Eur Respir J. 2015;45:310-3.